Analisis Tren Bulanan Status Gizi Balita sebagai Dasar Perencanaan Promosi Kesehatan di Tingkat Desa Tahun 2025 - Nurul Ilmi; Ani Asram; Yuli Rahayu (Jurnal Promosi Kesehatan Poltekkes Bengkulu, 2026)
Dynamic monitoring of toddler nutritional status is a fundamental pillar for the early detection of growth disturbances within rural communities. This study aims to map monthly nutritional status trends based on Weight-for-Age (WAZ), Height-for-Age (HAZ), and Weight-for-Height (WHZ) indicators in Bukit Indah and Wattang Soreang Villages throughout 2025 . The research employed a quantitative descriptive design with a longitudinal approach. Secondary data were collected from routine nutrition surveillance reports from January to December 2025, involving all registered toddlers in the study areas via total sampling . The findings revealed significant fluctuations across all nutritional indicators, peaking between August and October. Stunting cases rose sharply from 86 children in January to 229 in October. Additionally, a double burden of malnutrition was identified, characterized by a simultaneous increase in obesity and undernutrition cases. Spatial disparities were observed, with Bukit Indah Village consistently contributing a higher case burden compared to Wattang Soreang Village . This study confirms that toddler nutritional status is influenced by temporal and seasonal factors. Health promotion practitioners are encouraged to develop a "Strategic Health Promotion Calendar" by strengthening nutrition education in the second quarter (April–June) as an anticipatory measure before peak periods to enhance the effectiveness of village-level interventions.